Religion as an influencing factor of right-wing, left-wing and Islamist extremism: findings of a Swiss youth study - Kamenowski, Maria (PLOS ONE, 2021)
In criminological research the relationship between religion and delinquency has received great attention. Religiosity has been shown to be a protective factor for violent behaviour, drug use and other types of crime. In contrast, the relationship between religion and extremism was rarely investigated and then almost exclusively in relation to Islamist extremism. This paper presents results of a youth survey on extremism in Switzerland. A total of 8317 young people in ten cantons were interviewed about right-wing, left-wing and Islamist extremism. The study allows in a unique way to analyse religion, religiosity and religious attitudes in relation to three forms of extremist attitudes. The results show that religion is an important influencing factor of extremism, but religious affiliation and religiosity are less important than specific religious attitudes such as religious tolerance and religious exclusivity.